Edukasi Slow Deep Breathing Exercise nUntuk Mengatasi Hipertensi Pada Posyandu Lansia Abadi 9 - Isnaini Herawati; Muhammad Lukman Hakim; Hafiza Amalia; Aprilia Nurlita Dwi Putri; Arif Pristianto; Cartika Volta Pradanov; Amalia Prasetyaningtyas (Universitas Pendidikan Indonesia Kampus Purwakarta, 2023)
Hypertension is one of the problems that are often found in the elderly. Hypertension is a health problem that is quite dangerous in the world, due to factors that lead to cardiovascular disease such as heart attack, heart failure, stroke and kidney disease where ischemic heart disease and stroke are the two main causes of death in the world. One of the non-pharmacological therapies that can be done by people with hypertension is relaxation techniques. Slow deep breathing exercise is a relaxation technique that is realized to function to regulate deep and slow breathing to overcome hypertension. This counseling was carried out at the Abadi 9 Gonilan Elderly Posyandu, Sukoharjo with the aim of providing information and knowledge about promotive and preventive efforts in dealing with hypertension problems and counseling was also assisted with leaflet media, as well as question and answer sessions to measure the level of knowledge of the residents. The result of this service activity was an increase in participants knowledge about hypertension and Slow Deep Breathing Exercise from the category of sufficient knowledge to the category of good knowledge.